Innovation impulse - Abdul Razak, Mariatulqabtiah (Universiti Putra Malaysia Press, 2016)
A perfect blend of design and innovation could serve as catalysts for future change. Designers offer knowledge and competencies to enable innovators envisage new ideas, with the ultimate aim of finding better and long-lasting solutions, by pushing boundaries and changing the norm. Inordinate power of good design will lead to invention of products or services with greater value and encouraging demand.